If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2ab + -14ab = 0 Combine like terms: 2ab + -14ab = -12ab -12ab = 0 Solving -12ab = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '-12'. ab = 0 Simplifying ab = 0 The solution to this equation could not be determined.
| 2r-3s-2r-3s= | | 5x+3+7x-9=v | | 15n-14y-14n-14y= | | f(x)=8*t^3-33*t^2+27*t | | x^3+8x-12=0 | | x=ln(2a) | | 6.50x+1.50y=414 | | d+2d-8=34-3d | | 6x+10=8x-2 | | log(x-10)=2-(log(x-1)) | | -3d+4=-2d+10 | | log(x-10)=2-log(x-1) | | 6w-(7x-2w)+4= | | 2d+3=8+d | | 2d+3=32 | | 3p-2=100 | | 3/x-12=x-4 | | 2(1x+4)=30 | | ln(2a)=0 | | x^2+2x-1=5x+3 | | -(-2w-x)+4(-6x-5w)= | | 2x+3=5-2 | | 3x/12=6 | | -x/4-5=7 | | C/3+4=-1 | | 5m+27+4m=72 | | 4-a/8=-3 | | log(x)+log(x+5)=log(x+4) | | 4-8m= | | 2(x+7)=10-2x+3 | | 2(x+7)=-8+28+2x | | 1.6(x-2.8)=(0.2+1.5)-0.7 |